2011
DOI: 10.1371/journal.pone.0020305
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference of Unconscious Attentional Bias in High Trait Anxiety Individuals

Abstract: By combining binocular suppression technique and a probe detection paradigm, we investigated attentional bias to invisible stimuli and its gender difference in both high trait anxiety (HTA) and low trait anxiety (LTA) individuals. As an attentional cue, happy or fearful face pictures were presented to HTAs and LTAs for 800 ms either consciously or unconsciously (through binocular suppression). Participants were asked to judge the orientation of a gabor patch following the face pictures. Their performance was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…However, we suggest that this forms only part of the picture pertaining to VA and female nurses being at greater risk. High trait anxiety is associated with attentive processing and may influence a processing bias in threat-related stimuli (Tan et al 2011). Some studies have suggested gender differences in processing potential threat or threat-related stimuli, where females are more sensitive to threatening stimuli than males and potentially could overestimate the threat involved (McClure 2000, Goos & Silverman 2002, McClure et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, we suggest that this forms only part of the picture pertaining to VA and female nurses being at greater risk. High trait anxiety is associated with attentive processing and may influence a processing bias in threat-related stimuli (Tan et al 2011). Some studies have suggested gender differences in processing potential threat or threat-related stimuli, where females are more sensitive to threatening stimuli than males and potentially could overestimate the threat involved (McClure 2000, Goos & Silverman 2002, McClure et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The current study investigated the cognitive processing of interpersonal information under conscious or subconscious conditions in both schizophrenia patients and healthy controls using the CFS approach. This paradigm has been widely used in subconscious studies (Jiang et al ., ; Tan et al ., ; Yang et al ., ; Anderson et al ., ; Stein and Sterzer, ; Vizueta et al ., ; Willenbockel et al ., ; Gray et al ., ; Troiani and Schultz, ; Akechi et al ., ; Kring et al ., ; Doi and Shinohara, ). As it was a demanding task that would be confounded by cognitive functions, mood, and anxiety, we included age, IQ score, BDI score, and SAS score as confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and his colleagues investigated the effect of invisible images on the distribution of spatial attention by use of the binocular rivalry paradigm and found that an 800‐ms presentation of the unconscious images could result in attentional bias (Jiang et al ., ). This paradigm has been widely used in subconscious studies of sexual orientation (Jiang et al ., ), nicotine addiction (Yan et al ., ), depression (Yang et al ., ), anxiety disorders (Tan et al ., ), and autism spectrum disorder (Akechi et al ., ). Most studies using the CFS paradigm have explored the subconscious processing of affective stimuli to assess social cognition and social performance (Jiang et al ., ; Tan et al ., ; Yang et al ., ; Anderson et al ., ; Stein and Sterzer, ; Vizueta et al ., ; Willenbockel et al ., ; Gray et al ., ; Troiani and Schultz, ; Akechi et al ., ; Kring et al ., ; Doi and Shinohara, ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that there was a gender difference in the relationship between attentional bias and social anxiety, and we further showed that this is due to the gender difference in DD from threat. Several studies have supported the fact that there are significant gender differences in the relationship between attentional bias and emotional processing (Merritt et al, 2007; Tan et al, 2011; Tran et al, 2013; Kinney et al, 2016), but they do not focus on the relationship between social anxiety and a subcomponent of attentional bias to threat. Our results provide further evidences for gender differences in attentional bias among socially anxious individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have included male and female subjects, but the relationship between attentional bias and social anxiety may be different for males and females. Evidence has supported there is significant gender difference in attentional bias to threat among individuals with anxiety, including high trait anxiety, general anxiety, and social anxiety (Merritt et al, 2007; Tan et al, 2011; Tran et al, 2013; Kinney et al, 2016). For example, in a study involving 82 adolescents, Zhao et al (2014) found significant positive correlation between the level of social anxiety and attentional bias to social threat for males, but not for females.…”
Section: Introductionmentioning
confidence: 99%